ANALYSIS OF VEGETATION STRUCTURE AND COMPOSITION AT NATURAL PEAT SWAMP FOREST, SINAR WAJO VILLAGE, JAMBI - Adventiaputri, Ajeng
Land conversion from natural forest to oil palm plantations continuously occurring in Jambi and causing land degradation and further decreasing the diversity of flora. The decreased flora species phenomenon will lead to loss of the ecosystem function as a clean water producer, flood prevention, and diversity of food sources, and fiber. Restoration of flora species diversity need to be done on degraded peatlands due to land conversion. The study of composition, structure, and dominance of vegetation of Sinar Wajo Natural Degraded Peat Swamp Forest expected to be used as a reference of native flora species in degraded peat forest restoration. The study was conducted in a Natural Secondary Peat Swamp Forest in Sinar Wajo Village area with a depth of 6m peat. Research sites are adjacent to burning peatland forests and canals. The transect is made at a distance of 230m from the canal and aligns the canal to the west along 220m. Six quadrat plots are made along the transect systematically with 20m spacing between plots. The plot is made with a size of 20m × 20m for trees, 10m × 10m for poles, 5m × 5m for saplings, and 2m × 2m for seedlings. Data of plants species and trees diameter (Diameter> 20cm), pole (10cm <Diameter <20cm), stakes (Diameter <10cm and Height> 1.5m), seedlings (Height <1.5m) were recorded. Herbariums are made to be identified in the laboratory for unidentified species in the field. The results showed the total density was 77 individuals / 0.24ha. Species richness in Sinar Wajo Nature Natural Forest as a whole there are 20 species of flora in tree habitus consisting of 11 species at tree level, 6 types at pole level, 7 types at stake, and 5 species at seedling level. The main compositions of native peatland forests in Sinar Wajo are Dyera sp, Shorea sp, Dipterocarpus sp, Gluta renghas, Palaquium sp1, Palaquium sp2, Archidendron clypearia, Eusideroxylon zwageri, Koompassia malaccensis, Mallotus paniculatus, and Dillenia sp. The vegetation structure was dominated by 7292 individuals / ha seedlings, followed by 1267 individuals / ha in diameter class less than 10cm, then 233 individuals / ha 10cm-20cm diameter class, and 104 individuals / ha in diameter class above 20cm. Important plants species in the Sinar Wajo Village Peat Natural Forest are Shorea sp. (67.8%.) at the tree level, Archidendron clypearia (112.8%) at the pole level, Syzygium sp. (137%) at the sapling level and at unidentified seedling level (86%).